Konstruksi Masyarakat Narmada Terhadap Komoditas Malean Sampi dalam Bingkai Pariwisata - Ririn Ayu Prastika; Nur Rahmi; Diki Wahyudi; Oryza Pneumatica Indrasari (Universitas Mataram, 2021)
This study aims to describe the social construction of the Narmada community towards the malean sampi commodity in the frame of tourism. This study uses primary data analysis methods with the help of the theory of Peter L. Berger and Thomas Luckman about social construction. The results of the study stated that Malean Sampi is a tradition of the Nyurlembang Village Community in Narmada District from ancient times until now. This tradition is an expression of gratitude for the abundance of crops and has finished working on the fields. Malean Sampi is the result of the social construction of society which is formed from social interactions and different patterns of community behavior, through 3 (three) dialectical processes, first, externalization is reflected in the background and traditional management of Malean Sampi in the form of rituals, clothing, and accessories. supporter. Second, objectivation can be seen from the institutionalization, values ​​, and rules of the village government and the Malean Sampi Pade Girang group. Third, internalization can be seen from the socialization process of the community and the village government to preserve local culture, by forming cultural commodities, namely the Malean Sampi Pade Girang Group. Malean Sampi has changed following the times, initially, the Malean Sampi tradition was a habit repeated by the people of Nyurlembang, but now Malean Sampi can become a symbol of life in various fields, be it economic, social, cultural and political.